Mycobacterium bovis infection in cats: Zoonotic transmission - Barandiaran, Soledad; Marfil, Maria Jimena; Yaafar, Natalia; Ferrer, María Fernanda; Fajardo, Sandra; Salvador, María Fernanda; Biscia, Mariana; Zumarraga, Martin Jose; Sarradell, Javier Eduardo (Wiley, 2025)
Tuberculosis caused by Mycobacterium bovis is an infectious disease of worldwide relevance, with a growing concern for its zoonotic potential. Although cattle are the primary host, infections in companion animals have been reported, raising new public health concerns. Methods: Four cases of M. bovis infection in two cohabiting cats and two humans, one being the pet owner and the other a veterinarian, are analysed. Microbiological and molecular diagnostic techniques were employed, including culture, PCR, and genotyping through spoligotyping. Results: The presence of M. bovis was confirmed in both felines, identifying the same spoligotype (SB0140). Subsequently, the infection was documented in the pet owner, who had no history of contact with livestock, and in a veterinarian who sustained a needlestick injury during sample collection. Conclusions: These findings highlight the risk of zoonotic tuberculosis originating from companion animals, even in the absence of direct exposure to livestock. The results underscore the need to strengthen diagnostic and surveillance strategies in non-traditional species and emphasise the importance of adopting a comprehensive One Health approach to prevent and mitigate transmission between animals and humans, particularly in regions where bovine tuberculosis is endemic.